E. Coli Infections - Importance of Early Diagnosis and Efficient Treatment 2020
DOI: 10.5772/intechopen.91677
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Deletion of Type III Secretion System Effectors in Enteropathogenic E. coli Unveils the Role of Non-LEE Effectors in A/E Lesion Formation

Abstract: Enteropathogenic E. coli (EPEC) is a diarrheagenic human pathogen. The hallmark of EPEC infection is the formation of the attaching and effacing (A/E) lesion in the intestinal epithelial cells, characterized by the effacement of brush border microvilli and the intimate bacterial attachment to the enterocyte in actinrich pedestal-like structures. The locus of enterocyte effacement (LEE) in the EPEC genome encodes a type III protein secretion system (T3SS) that translocates multiple effector proteins into the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…We have previously shown that the primary virulence factor of EHEC, Shiga toxin, suppresses noncanonical inflammasome responses 20 . Similarly, T3SS effectors such as Tir and non-LEE encoded effector (Nle) proteins of EHEC inhibit TLR4-dependent NFκB-and MAPK-responses [57][58][59][60][61][62][63][64] .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the primary virulence factor of EHEC, Shiga toxin, suppresses noncanonical inflammasome responses 20 . Similarly, T3SS effectors such as Tir and non-LEE encoded effector (Nle) proteins of EHEC inhibit TLR4-dependent NFκB-and MAPK-responses [57][58][59][60][61][62][63][64] .…”
Section: Discussionmentioning
confidence: 99%